Dengue Fever Complicated by Sickle Cell Crisis with Multiple Splenic Infarcts - Prusty, B Saroj Kumar; Ramineni, Kiran Kumar; Ingle, Abhijeet; G, Krishna Mohan Reddy; Perveen, Safina; Momin, Majed Abdul Basit (International Journal of Human and Health Sciences (IJHHS), 2021)
Dengue infections typically present with fever and thrombocytopenia. Although good number of patients improve with supportive care, few can have a fulminant course with multiorgan dysfunction. In endemic zone co-occurring illness like Sickle cell disease can contribute to poor outcome. Various splenic complications of Sickle cell disease include massive splenomegaly with sequestration, large infarcts and abscess requiring splenectomy. We report an interesting case of dengue fever, who developed shock and acute abdomen during hospital stay. Further evaluation revealed multiple splenic infarcts with correlating histopathology and etiological work up including hemoglobin electrophoresis helped in the de novo detection of the underlying sickle cell trait. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 519-524